(untitled) (Revista Argentina de Musicología, 2025)
This article is the result of research that explored the infinite relationship between politics and music. Its objective is to elucidate and analyze the ways in which a youthful political identity was articulated within the spaces of popular folk music in Rosario during the period from 1959 to 1976. The central hypothesis of this study is that, within the framework of the Rosario folk music gatherings (peñas), studied as a ritual, a particular youthful political subjectivity was articulated. This subjectivity was constructed through the overlapping of three dimensions that shape political identity: otherness, representation, and an approach to tradition. The methodology employed is qualitative, including work with secondary sources, specialized literature, popular folk songs, and open-ended interviews with relevant actors, particularly those who attended and participated in folk music gatherings during the period in question.